Pleomorphic adenoma –soft palate: A case report - Rajeshwari G; Sundara Raju H (Journal of All India Institute of Speech and Hearing, 2013)
Pleomorphic Adenoma is the most common benign tumor of the salivary gland. It predominantly occurs within the parotid gland, less than 3% of salivary gland tumors have been reported of pleomorphic adenoma of minor salivary gland. A case of a 47 year old woman presenting with Pleomorphic Adenoma of minor salivary gland is reported. Though Malignancies are very common in the minor salivary glands occasionally benign tumors like Pleomorphic Adenoma can also occur. Fine needle aspiration cytology study has to be established before planning surgery. The incidence of recurrences is low when a wide excision is planned.